Muhadhoroh and English Public Speaking Skills: Benefits, Challenges, and Strategies - Budianto, Lestari (Universitas PGRI Adi Buana Surabaya, 2023)
In the modern era, Islamic boarding school education has changed forms of adaptation to the times. One of them is the existence of the term Modern Islamic Boarding School where the education system combines national and international curricula and adapts to the needs of the students. Extracurricular activities are one of the activities that exist in modern Islamic boarding schools. This activity is known as Muhadhoroh. This study explores Muhadhoroh and English-speaking skills related to the benefits, challenges, and strategies for these activities. This study uses a descriptive qualitative method. The research data were obtained from interviews, observations, and documentation while the participants in this study were three English teachers who teach at Amanatul Ummah Islamic boarding school both Indonesian and foreign teachers. The research data were analyzed in four stages, namely data collection, data display, data reduction, and conclusion. The results of this study indicate that Muhadhoroh could provide opportunities for students to develop talents in the field of English public speaking skills because students had the opportunity to perform various kinds of English performances in public. Related to challenges, this activity has challenges including preparation, time management, and facilities. Even so, several strategies could be taken to overcome these challenges, including arranging preparation and performance schedules, utilizing free time and shifting school schedules into preparation and performance schedules, as well as adding facilities by renting equipment to other parties during activities. This study is limited in location and the number of participants who are only in one Islamic boarding school and the type of research instrument. It is recommended for further research to be able to conduct similar research by adding variations of participants and Islamic boarding schools as well as adding variations of research instruments